The need to address skin pathologies amidst flooding crisis in Pakistan - Nasir, Moosa (Journal of the Pakistan Medical Association, 2023)
Madam, As the monsoon approached, Pakistan was ravaged by extreme rainfalls and deadly flooding which affected 33 million people, including 16 million children. (1) With this disaster came a horde of water- borne diseases. The officials recorded over 600,000 people reporting to the relief camps with illnesses, including gastroenteritis, skin infections, acute respiratory infection, cases of malaria, and bites ranging from insects to dogs. (2) Among these diseases, skin pathologies are the second most common complaint reported by the flood- affected population and even though they might be the second most common cause of morbidity; small wounds, lacerations, punctures and skin infections resulting from them are the first to appear in the impact phase after any hydrologic disaster, including floods, rendering it crucial to address skin related pathologies as a priority. (3) Skin diseases may not seem important, with malnutrition, gastroenteritis, malaria and dengue looming in the relief camps, Still the lack of attention can lead to disastrous effects ranging from atypical bacteria like vibrio vulnificus and mycobacterium marinum causing skin infections, infestations with scabies to necrotising soft tissue infection (NSTI) complicating traumatic soft tissue injuries (3.4). This significantly increases the burden of diseases and puts great stress on the already crippled healthcare system in the affected areas and also leads to increase suffering which could easily be avoided by timely precautions and preventative measures taken to decrease the burden. Unfortunately, this isn’t the first time Pakistan has been dealing with the aftermath of a hydrologic disaster. In 2010, Pakistan faced a flood crisis resulting in 1600 deaths and 143,780 skin infections as the third most common cause of illness. (5) The numbers of infections aren’t different from the ones being reported in the recent monsoon floods. This warrants an imminent need to develop a flood response system to reduce the risk of dermatological diseases, tailored to the risk and population of the area. Health awareness programs to educate the masses about practicing good hygiene, making use of sunshine to deal with diseases like scabies which are rampant in the camps, and active involvement of community workers with basic first aid kit to treat minor cuts, lacerations could significantly reduce the morbidity and mortality associated with these conditions. ---Continue